Practical Route to the Left Wing of CTX1B and Total Syntheses of CTX1B and 54‐deoxyCTX1B. Issue 6 (21st December 2014) - Yamashita, Shuji; Takeuchi, Katsutoshi; Koyama, Takuya; Inoue, Masayuki; Hayashi, Yujiro; Hirama, Masahiro
Abstract Ciguatoxins, the principal causative agents of ciguatera seafood poisoning, are extremely large polycyclic ethers. We report herein a reliable route for constructing the left wing of CTX1B, which possesses the acid/base/oxidant‐sensitive bisallylic ether moiety, by a 6‐exo radical cyclization/ring‐closing metathesis strategy. This new route enabled us to achieve the second‐generation total synthesis of CTX1B and the first synthesis of 54‐deoxyCTX1B.